Cartel Practices in Indonesian Tyre Industry: Assessing the Role of the Indonesian Tyre Business Association: Praktek Kartel Pada Industri Ban Indonesia: Meninjau Peran Asosiasi Perusahaan Ban Indonesia - Susanto, Indra; Markoni, Markoni (Rechtsidee, 2023)
This study examines the legal standing of the Indonesian Tyre Business Association (APBI) in light of the KPPU Decision Number 08/Pdt.G/KPPU-I-2014 concerning tire cartel violations in the Indonesian automotive industry. Utilizing normative legal research methods focusing on positive legal norms, the study identifies and systematizes violations of business competition rules by six major APBI member companies between 2008 and 2012, and critically analyzes and interprets the evidentiary basis of these findings. The companies allegedly colluded on tire pricing, manipulating the market for Passenger Car Radial (PCR) tires and inducing unfair business competition. The study asserts that, while the APBI's role in facilitating this collusion was apparent, its legal liability remains unclear due to the association's ability to influence member practices without a binding enforcement mechanism. These findings raise critical implications for market competition and cartel law enforcement, necessitating a re-evaluation of the legal provisions surrounding business associations, especially in the context of Indonesia's anti-monopoly and unfair competition laws.Highlights: APBI's facilitation of cartel behavior among its members. Unclear legal liability of business associations in anti-competitive practices. Need for re-evaluation of legal provisions surrounding business associations. Keywords: Cartel, Indonesian Tyre Business Association (APBI), Unfair Business Competition, Competition Law, Indonesian Tyre Industry